ANALISIS USAHA DAN BAURAN PEMASARAN KERUPUK KULIT KABITA DI KELURAHAN TUAH KARYA KECAMATAN TAMPAN KOTA PEKANBARU - Putut Dwi Isrfansyah; Sisca Vaulina (UIR Press, 2024)
The utilization of RPH waste has developed into an agro-industrial venture focused on cowhide crackers. This research aims to examine (1) the features of entrepreneurs and the profiles of the businesses, (2) the production processes, technologies, costs, income, efficiency, and break-even point (BEP), and (3) the marketing strategies employed. A survey was conducted at the Kabita cowhide cracker enterprise located in Tuah Karya Village, Tampan District, Pekanbaru City. The data analysis was performed descriptively, incorporating both qualitative and quantitative approaches. The findings of this study indicate that: (1) Entrepreneurial and worker characteristics include being of productive age, possessing 12 years of education, having 1-5 years of business experience, and supporting 1-2 dependents. The Kabita cowhide cracker enterprise is categorized as a small-scale industry. (2) The production process is carried out traditionally, with variable costs amounting to Rp. 9,479,000, fixed costs of Rp. 69,655, and a gross income of Rp. 17,556,000. The net income reaches Rp. 8,027,891, yielding a return cost ratio (RCR) of 1.85. The marketing mix encompasses product offerings, pricing, distribution channels, and promotional activities.